Missed Vaccinations in Children during the COVID-19 Pandemic - Kiran Basavaraja; Suman Meenakshi Gururaja; Geetha Mannivanan; Santosh Srinivasiah (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: During the Coronavirus Disease 2019 (COVID19) pandemic, lockdown was imposed to break the rapid spread of infection which hampered many essential services. This included medical services and particularly the scheduled vaccinations among children. Consequently, many children missed or delayed vaccinations. Aim: To find the incidence and reasons for missed/delayed vaccination in children during the COVID-19 pandemic. Materials and Methods: This was a prospective hospital-based cross-sectional study done in the Department of Paediatrics, East Point College of Medical Sciences and Research Centre, Bengaluru, Karnataka, from March 2020 to February 2021.The total number of patients studied were 515. The samples included all children aged 0-10 years attending the paediatric Outpatient Department (OPD) for vaccination. Details about age, gender, address, parental details of education, occupation and income were recorded, using a questionnaire. Immunisation card was checked to ascertain whether any of the vaccines were missed or delayed and advice about catch up vaccination was given. The reasons for delay or missed vaccinations were recorded. Multivariate logistic regression was used to compare different classes of population with delay and as per schedule classes of children for individual vaccines. Results: The mean age of the population was 13.77 months. Delay in vaccinations was seen in 213 (41.35%) children, among among them were 94 (44.13%) girls, and 119 (55.86%) boys. Mean age of the population with delay /missed vaccinations were 21.23 months. Main cause cited in 88.2% cases for delayed /missed vaccination was fear of getting infected with Covid-19 during hospital visits. The vaccinations with most significant delay were pentavalent vaccination at 10 weeks with a mean age of delay being 1.1 month as per National Immunisation Schedule (NIS) and Typhoid vaccination as per in Indian Academy of Pediatrics (IAP) schedule with a mean age of delay of 5.2 months. The vaccinations were delayed in all socio-economic classes of the populations during the study period. Conclusion: The COVID-19 pandemic has hampered all healthcare services including immunisation. Intentional vaccine delay due to any reason by parents should be avoided and catch up immunisation should be given at the earliest.